Auto Whatsapp Sebagai Alternatif Layanan Perpustakaan pada Masa Pandemi Covid-19 di IAIN Curup - Maisonah Maisonah (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
Library is  to develop knowledge and information. Every information and knowledge in a library is obtained from several media; such as books; magazines; brochures; computers use networks and journals. Library services are management to manage all media information and knowledge. In March 2020 the Covid-19  enter Indonesia. One way to assist the government in preventing the spread of Covid-19 is to eliminate face-to-face lectures. In addition; library services are removed. Therefore; in order to keep library services running; one alternative is to use Auto WhatsApp. This application helps students in obtaining library services especially in obtaining a Fractivator-Free Library Information (CFL). The results of large-scale trials of SKBPP services with autowhatsapp to 73 users' responses resulted in 98.6% stating that users were satisfied with the service; 95.9% of users stated that SKBPP services with autowhtasapp were effective; 97.3% users easily used the application; 95.9% users stated that the information on the service was clear; and 97.3% of users stated that the use of sentences in autowhatsapp was easy to understand. From the research; it is concluded that Auto WhatsApp can be used as an alternative service during the Covid-19 pandemic and further development is needed